Synergistic remediation of Cd/Pb contamination in paddy soils using iron-based sulfur-rich material combined with foliar Zn fertilizer - Chen, Ting; Sun, Yuanyuan; Qin, Fanxin; Li, Chunxiang; Zhong, Lin; Wang, Jinjin; Huang, Wanyu; Wang, Haihe; Feng, Qiufen (Frontiers in Microbiology, 2026)
Addressing the limitations of single-technology approaches to mitigate cadmium (Cd) and lead (Pb) co-contamination in rice, this study elucidates the synergistic mechanism between iron-based soil immobilization and foliar zinc (Zn) barrier control. A pot experiment with four treatments was conducted: CK (control), FBA (foliar Zn fertilizer), IBS (iron-based sulfur-rich material), and ISF (IBS combined with Zn). The ISF treatment showed particularly remarkable efficacy. Compared to the CK, it increased rice biomass by 49.6%, reduced Cd and Pb concentrations in grains by 53.8 and 54.2%, respectively (to 0.2 mg/kg), and enhanced Zn accumulation by 311.8%. This treatment raised soil pH by 1.4 units, decreased bioavailable Cd and Pb by 31.2 and 18.5%, and promoted the transfomation of Cd into the Fe-Mn oxide-bound fraction (FMO, + 389.1%) and the residual fraction (RES, + 5.3%), while simultaneously increasing the FMO-bound proportion of Pb by 29.6%. Furthermore, ISF significantly enhanced soil enzyme activities (e.g., urease), increased total microbial OTUs with 187 unique OTUs, enriched Nitrospirotaphyla, Desulfobacterota, and Geobacterales, strengthened nitrogen/sulfur/iron cycling functions, and improved microbial network robustness. This research provides a theoretical foundation for heavy metal mitigation and nutritional fortification in rice production systems.